Hyperemia in head injury: can transcranial doppler help to personalize therapies for intracranial hypertension? - Gelormini, Camilla; Ioannoni, Eleonora; Scavone, Angela; Pisapia, Luca; Signorelli, Francesco; Montano, Nicola; Piastra, Marco; Caricato, Anselmo (Frontiers in Neurology, 2023)
The increase in cerebral blood flow is frequently observed after traumatic brain injury, and is associated with impaired autoregulation. This can lead to brain swelling and refractory intracranial hypertension, but the physiopathology of this condition is still not completely clear.Transcranial EcoDoppler (TCD) ultrasound offers a non-invasive and easily reproducible method for evaluating cerebral hemodynamics. Our results suggested that hyperemia was present in about one third of patients, and was associated with intracranial hypertension. According to other authors, hyperemia significantly preceded intracranial hypertension, providing a physiological basis for intervention aimed at reducing the vascular contribution to intracranial volume.TCD monitoring, if performed on a daily regular basis, can be a useful method to detect derangements of brain hemodynamics and to guide the therapy. It could be a tool for a cause-oriented therapy of intracranial hypertension.